Firm Ownership Structure and Intellectual Capital Disclosures - FIRER, Stephen (Institutional Knowledge at Singapore Management University, 2005)
The primary purpose of this study is to investigate the association between three ownership structure characteristics and voluntary intellectual capital (IC) disclosure practices. Data for this study is hand collected from the 2000 annual reports of 390 Singapore publicly traded firms. Empirical results indicate Singapore publicly traded firms more closely owned were less likely to voluntarily disclose IC related information than were those where executive directors had smaller holdings in the entity. Finally, findings indicate government linked corporations (GLCs) will likely make more voluntary IC disclosures than non-GLCs. Overall, this study makes several unique contributions to the literature. First, the present study provides the first large-scale analysis of evidence of the association between ownership structure and voluntary intellectual capital disclosure practices. The study also contributes by broadening the examination of intellectual capital disclosure practices beyond general descriptive overviews.